Tolerance to intraoral biofilms and their effectiveness in improving mouth dryness and modifying oral microbiota in patients with primary Sjögren’s syndrome: “Predelfi study” - Orliaguet, Marie; Fong, Shao Bing; Le Pottier, Laëtitia; Meuric, Vincent; Boisramé, Sylvie; Bonnaure-Mallet, Martine; Pers, Jacques-Olivier (Frontiers in Microbiology, 2023)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease characterized by exocrine gland dysfunction. No therapeutic strategy is sufficient on its own for the management of dry mouth and therapeutic innovations are required. This Predelfi study was a single-center, prospective, comparative, randomized, double-blind, cross-over controlled study with the primary objective of assessing the tolerance to and effectiveness of two adhesive biofilms (containing prebiotics and, sodium alginate, respectively) in patients with pSS and hyposialia (#NCT04206826 in ClinicalTrials.gov). Secondary objectives were to obtain initial data regarding the clinical effectiveness of such biofilms in the improvement of signs and symptoms related to dry mouth and potential changes in the oral microbiota. Ten pSS patients with pSS were included (9 females and 1 male) with a mean age of 58.1 ± 14.0 years. Tolerance to the prebiotic and sodium alginate biofilms was assessed by the patients (visual analog scale [VAS] score 66.7 and 87.6, respectively) and the practitioner (90 and 100, respectively). The absolute changes in the VAS scores at the start and end of each treatment period highlighted an improvement in mouth dryness for the sodium alginate versus the prebiotic biofilm. The VAS scores for other parameters (mouth burning sensation; taste alteration; chewing; swallowing and speech difficulties) remained globally comparable between the two groups. Unstimulated salivary flow showed no changes regardless of the biofilm used. Regarding the oral microbiota, the sodium alginate biofilm increased the abundance of the Treponema genus, whereas the use of the prebiotic biofilm as the first treatment increased the abundance of the genera Veillonella and Prevotella. Nevertheless, the prebiotic biofilm appeared to stimulate “milder” genera with regard to periodontal infections. Furthermore, pre-treatment with the prebiotic biofilm prevented the emergence of the Treponema genus induced by subsequent treatment with the sodium alginate biofilm, suggesting a potential protective effect.